Consumer ethnocentrism: Reconceptualization and cross-cultural validation - Sharma, Piyush (Palgrave Macmillan, 2015)
Consumer ethnocentrism (CE) is a popular construct in international marketing research and is generally measured using the CETSCALE, a reliable scale with proven predictive validity but with limited evidence about its construct validity, dimensionality and cross-cultural measurement invariance. This note addresses these gaps by reconceptualizing CE as an attitude construct consisting of three dimensions: (1) affective reaction, (2) cognitive bias and (3) behavioral preference. A revised CE scale (CES) is developed and tested using two empirical studies with adult consumers from four different countries (China, India, UK and USA), showing that CES is a reliable, valid and cross-culturally invariant scale and it explains greater variance than the CETSCALE and other similar scales, in customer evaluations and behavioral intentions for a wide range of products and services.